Preparation method of photochromic elastomer with both long-term coloring and fast fading properties
By preparing photochromic elastomers with dense hydrogen bond crosslinking networks, the shortcomings of existing photochromic materials in long-term storage of information and rapid fading are solved, and the effect of long-term stable coloring and rapid fading in indoor environments is achieved.
Patent Information
- Application Number
- CN202410730574.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-06-06
AI Technical Summary
Existing photochromic materials are difficult to store information for a long time in daily use environments, and are prone to fade under the action of oxygen or visible light, which limits their application on information storage media.
By preparing a photochromic elastomer that combines long-term coloring and rapid fading, a dense hydrogen bond crosslinking network is formed by using polymer monomers, photochromic unit dispersions, initiators and crosslinking agents. Obstructs oxygen diffusion and accelerates the fading process.
It realizes long-term stable coloring of photochromic elastomers in indoor environments, and quickly fades through 0.5wt% hydrogen peroxide solution, and has the characteristics of long-term storage and rapid erasure of information, which solves the application of existing photochromic materials in information storage. limitations in
Smart Images

Figure CN118546291B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of color-changing materials, and more specifically relates to a method for preparing a photochromic elastomer with both long-term coloring and rapid fading properties. Background Art
[0002] Photochromic materials have important application prospects in the fields of optical camouflage, information storage, etc. Currently, the widely studied photochromic materials include organic photochromic materials represented by derivatives such as spiropyran and diarylethene, and inorganic photochromic materials represented by polyoxometalates and tungsten trioxide.
[0003] From the perspective of the coloring and fading mechanism of photochromic materials, the coloring and fading of organic photochromic materials are achieved through photoisomerization, that is, the molecular structure changes when exposed to light. The spirocyclic structure of molecules such as spiropyran and diarylethene will open after being exposed to ultraviolet light, resulting in color change (i.e., the coloring process); after being exposed to visible light, the opened spirocyclic structure will close again, and the color will be restored (i.e., the fading process). Taking polyoxometalates and tungsten trioxide as examples, the coloring mechanism of inorganic photochromic materials is generally believed to be the double injection theory model proposed by Faughnan in the 1970s. In simple terms, it is a light-driven chemical reaction that allows the metal atoms (represented by Mo and W) in the inorganic photochromic unit to obtain an electron, thereby achieving color change. The fading process of inorganic photochromic materials is generally achieved by oxygen in the air. Oxygen uses its oxidizing ability to take away the electrons obtained by metal atoms such as Mo and W, thereby achieving the fading process.
[0004] The photochromic materials currently being studied have this type of reversible coloring and fading behavior, and are erasable in application scenarios, so they are considered to be erasable information storage media. However, from their fading principles, we can see that whether it is an inorganic photochromic material or an organic photochromic material, their common feature is that they will fade under daily use conditions. Inorganic photochromic materials will fade when exposed to oxygen after coloring, and organic photochromic materials will fade when exposed to visible light. These characteristics make it difficult for these materials to achieve long-term information storage, which greatly limits the application of such materials in information storage media. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a photochromic elastomer having both long-term coloring and rapid fading properties, so as to solve the problems existing in the above-mentioned prior art and achieve long-term coloring and rapid fading of the photochromic elastomer.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a photochromic elastomer having both long-term coloring and rapid fading properties, the steps comprising:
[0008] The initiator, the crosslinking agent and the urea are dissolved in water, and then the photochromic unit dispersion and the polymer monomer are added in sequence, and finally the initiator auxiliary agent is added, and after uniform mixing, the mixture is allowed to stand for curing and dried to obtain the photochromic elastomer.
[0009] Furthermore, the photochromic unit dispersion is prepared by dispersing the photochromic unit in water, with a mass fraction of 5 to 20%.
[0010] Furthermore, the photochromic unit in the photochromic unit dispersion includes tungsten trioxide.
[0011] Furthermore, the initiator includes ammonium persulfate or potassium persulfate.
[0012] Furthermore, the cross-linking agent includes N,N-methylenebisacrylamide or polyethylene glycol diacrylate.
[0013] Furthermore, the photochromic unit includes tungsten trioxide.
[0014] Furthermore, the average particle size of the photochromic unit is 15 to 100 nm.
[0015] Furthermore, the polymer monomer includes hydroxyethyl acrylate.
[0016] Furthermore, the initiator auxiliary comprises tetramethylethylenediamine.
[0017] Furthermore, the usage ratio of the polymer monomer and the photochromic unit dispersion is 4-20 mmol:0.5 mL.
[0018] Furthermore, the molar ratio of the polymer monomer to urea is 4-20:0-20.
[0019] Furthermore, the molar ratio of the polymer monomer, the initiator and the cross-linking agent is 4-20:0.01-0.05:0.002-0.1.
[0020] Furthermore, the molar ratio of the initiator to the initiator auxiliary is 0.01-0.05:0.01-0.05.
[0021] Furthermore, the volume ratio of the photochromic unit dispersion to water is 5:16.
[0022] Furthermore, the static curing time is 10 to 60 minutes.
[0023] Furthermore, the drying temperature is 40-80°C.
[0024] The second technical solution of the present invention is to provide a photochromic elastomer prepared by the above preparation method.
[0025] The photochromic elastomer prepared by the invention can be stably colored for a long time in an indoor environment after being colored by light. When fading, it only needs to apply a 0.5wt% concentration of hydrogen peroxide solution on the colored part, and the fading can be completed in more than ten minutes.
[0026] When the elastomer prepared by the present invention is irradiated with ultraviolet light, the electrons in the valence band are excited to the conduction band, generating electron-hole pairs, and then the photogenerated electrons are captured by W(VI) to generate W(V). At the same time, the photogenerated holes oxidize the reduced species inside or on the surface of the film to generate protons H + , injected into the interior of tungsten trioxide, combined with the reduced oxide to form blue tungsten bronze H x WO3, blue is the result of the electron transition from the W(V) valence band to the W(VI) conduction band; fading is achieved by oxidizing W(V) to W(VI) through the oxidation of an oxidant (such as oxygen, hydrogen peroxide, etc.), so that the aforementioned transition process no longer occurs.
[0027] It is worth noting that the fading process of tungsten trioxide in the prior art is driven by oxygen, while the polymer network of the elastomer prepared by the present invention contains a large number of hydroxyl groups (derived from hydroxyethyl acrylate monomers), forming extensive hydrogen bond interactions, as non-covalent crosslinking widely present inside the polymer network. Such a dense crosslinking network limits the diffusion of oxygen inside the elastomer. At the same time, the polymer network and the surface of tungsten trioxide nanoparticles will also form strong hydrogen bond interactions, which will hinder the interaction between tungsten trioxide and oxygen molecules. The elastomer prepared by the present invention has the characteristic of stable coloring in the air.
[0028] When the elastomer is treated with hydrogen peroxide solution, due to the hydrophilicity of polyhydroxyethyl acrylate, it will swell. During swelling, the elastomer absorbs a large amount of hydrogen peroxide. At the same time, water molecules will interfere with the hydrogen bond interaction mentioned above. The swelling process also significantly increases the distance between molecular chains and the distance between the molecular weight and the tungsten trioxide nanoparticles, thereby significantly accelerating the fading process.
[0029] The third technical solution of the present invention is to provide an application of the above-mentioned photochromic elastomer in long-term information storage and rapid erasure materials.
[0030] The present invention discloses the following technical effects:
[0031] The photochromic elastomer prepared by the present invention, on the one hand, improves the crosslinking density of the polymer network through the strong hydrogen bonding between the polymer molecular chains, hindering the diffusion of oxygen molecules; on the other hand, through the strong hydrogen bonding between the polymer molecular chains and the photochromic unit, the interaction between the photochromic unit and oxygen is hindered, so that the photochromic unit cannot fade under the action of oxygen, thereby realizing that the photochromic elastomer will not fade under visible light irradiation and / or exposure to air, providing the possibility for long-term effective storage of information. At the same time, it also has the ability to be erased, and the fading process can be achieved within a dozen minutes by treating with 0.5% concentration of hydrogen peroxide. The photochromic elastomer has both long-term information storage and fast erasing characteristics, solving the problem of limitations faced by existing photochromic materials in information storage applications.
[0032] The main component of the photochromic elastomer prepared by the present invention is a polymer monomer, and there are a large number of hydroxyl groups on the side chain of this polymer. These hydroxyl groups can form strong hydrogen bond interactions with oxygen atoms on the surface of the photochromic unit, thereby hindering the interaction between oxygen and the photochromic unit and inhibiting the fading process. In addition, the widespread hydrogen bond interaction also allows the polyhydroxyethyl acrylate to form strong interactions with each other, making it difficult for oxygen to diffuse into the elastomer, further reducing the opportunity for tungsten trioxide to interact with oxygen, and further inhibiting the fading process. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0034] Figure 1 The diagram shows the photochromic process of the elastomers prepared in Examples 1 to 5 as the UV irradiation time increases;
[0035] Figure 2 The surface reflectivity of the elastomer prepared in Example 1 under different UV irradiation times;
[0036] Figure 3 The graph is a trend chart of the surface reflectivity change at 471 nm of the elastomers prepared in Examples 1 to 5 under different UV irradiation times;
[0037] Figure 4 The fading process of the elastomers prepared in Examples 1 to 5 when treated with a 5 wt % hydrogen peroxide solution is shown;
[0038] Figure 5 The fading process of the elastomers prepared in Examples 1 to 5 after being exposed to air is shown in the figure;
[0039] Figure 6 The surface reflectivity variation trend diagram at 471 nm of the elastomers prepared in Examples 1 to 5 after exposure to air;
[0040] Figure 7 This is a diagram showing the fading process of the elastomer prepared in Comparative Example 3 after being exposed to air after being irradiated with ultraviolet light for 5 minutes;
[0041] Figure 8 This is a diagram showing the fading process of the elastomer prepared in Example 3 when treated with a 5wt% hydrogen peroxide solution;
[0042] Fig. 9 This is the fading process of the inorganic photochromic material based on polyoxometalate involved in Comparative Example 1;
[0043] Fig.10 The coloring and fading process of the spiropyran-based organic photochromic elastomer involved in Comparative Example 2;
[0044] Fig.11 The breaking stress and breaking elongation of the elastomers prepared in Examples 1 to 5;
[0045] Fig.12 is the elastic modulus of the elastomer prepared in Examples 1 to 5. DETAILED DESCRIPTION
[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0047] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0051] Unless otherwise specified, room temperature and normal temperature referred to in the present invention refer to 20-30°C.
[0052] The cross-linking agent used in the specific embodiment of the present invention is N,N-methylenebisacrylamide, which contains α and β unsaturated carbonyl groups at both ends. Therefore, other cross-linking agents defined in the present invention can be equally replaced in the specific embodiment without affecting the realization of the technical effect.
[0053] The preparation steps of the photochromic unit dispersion used in the specific embodiment of the present invention are as follows: adding a photochromic unit (tungsten trioxide) with an average particle size of 50 nm into water, and obtaining a photochromic unit (tungsten trioxide) dispersion with a mass fraction of 20% after ultrasonic dispersion.
[0054] Example 1
[0055] The preparation steps of the photochromic elastomer with both long-term coloring and fast fading properties are as follows:
[0056] S1, 0.05 mmol of initiator (ammonium persulfate), 0.1 mmol of cross-linking agent (N,N-methylenebisacrylamide), and 5 mmol of urea were dissolved in 1.6 mL of water to prepare a mixed solution;
[0057] S2, 0.5 mL of photochromic unit (tungsten trioxide) dispersion and 20 mmol of polymer monomer (hydroxyethyl acrylate) were added to the mixed solution in sequence, and finally 0.05 mmol of initiator auxiliary (tetramethylethylenediamine) was added to obtain a prepolymer solution;
[0058] S3. The prepolymer solution is allowed to stand at room temperature for half an hour to complete polymerization and curing, and then placed in an oven and heated at 60° C. for 3 hours to remove all moisture to obtain a photochromic elastomer.
[0059] Example 2
[0060] Compared with Example 1, the only difference is that the amount of urea used is 10 mmol.
[0061] Example 3
[0062] Compared with Example 1, the only difference is that the amount of urea used is 15 mmol.
[0063] Example 4
[0064] Compared with Example 1, the only difference is that the amount of urea used is 20 mmol.
[0065] Example 5
[0066] Compared with Example 1, the only difference is that the amount of urea used is 0 mmol.
[0067] Comparative Example 1
[0068] The preparation steps of inorganic photochromic materials are as follows:
[0069] In 2018, an international academic journal described a photochromic material based on polyoxometalates (ACS Appl. Mater. Interfaces 2018, 10, 13975-13984). The material uses acrylamide as a monomer and introduces ammonium paramolybdate, a polyoxometalate, to obtain a hydrogel material that can achieve photochromic properties. The results of the study showed that the obtained photochromic material can undergo significant color changes within 30 seconds under ultraviolet light, and the color completely fades after exposure to air for 6.5 hours. Compared with the patent of this invention, the photochromic material reported in this academic paper will fade significantly when exposed to air and does not have the characteristics of long-term coloring.
[0070] Fig. 9 This is the fading process of the inorganic photochromic material based on polyoxometalate involved in Comparative Example 1.
[0071] Comparative Example 2
[0072] The 2023 international academic journal ACS Applied Polymer Materials described a series of spiropyran-based organic photochromic elastomers (ACS Appl. Polym. Mater. 2023, 5, 1696-1706). This series of elastomers are composed of monomers such as styrene, methyl methacrylate, and butyl acrylate, and photochromic properties are achieved by introducing spiropyran derivatives during the polymerization process. The study showed that the resulting spiropyran-based photochromic elastomer can undergo significant color changes after 15 seconds of irradiation with ultraviolet light, and the color completely fades after 15 minutes of irradiation with visible light. Compared with the patent of this invention, the photochromic elastomer reported in this academic paper will fade significantly when exposed to visible light and does not have the characteristics of long-term coloring.
[0073] Fig.10 This is the coloring and fading process of the spiropyran-based organic photochromic elastomer involved in Comparative Example 2.
[0074] Comparative Example 3
[0075] The difference between Comparative Example 3 and Example 5 is that ethanol is used instead of water as the dispersant of tungsten trioxide nanoparticles, and butyl acrylate is used instead of hydroxyethyl acrylate.
[0076] Test example
[0077] In a specific embodiment of the present invention, tungsten trioxide nanoparticles are photochromic units, which can realize the photochromic process; hydroxyethyl acrylate is a polymer monomer, which can form a three-dimensional network structure after polymerization; N,N-methylenebisacrylamide is a crosslinking agent, and the three-dimensional network structure formed by the polymer monomer is realized by it; ammonium persulfate is an initiator, and the free radicals generated when it decomposes start the polymerization process of hydroxyethyl acrylate; tetramethylethylenediamine is an initiator auxiliary, which can promote the decomposition of ammonium persulfate, so that it can realize the initiation effect at room temperature; urea is used to adjust the mechanical properties and fading speed of the elastomer.
[0078] Experimental process of photochromic coloration and fading
[0079] The photochromic elastomers prepared in Examples 1 to 5 were subjected to coloring and fading experiments, and the process steps are as follows:
[0080] Coloring process: The elastomer was placed under a 365nm LED UV lamp, and taken out every one minute to observe, take pictures, and measure the spectrum. It can be observed that as the irradiation time increases, the elastomer changes from a lighter sky blue to a dark blue. The diffuse reflection absorption spectrum can be observed that as the irradiation time increases, the surface reflectivity of the elastomer decreases. The changes in the coloring process are as follows: Figures 1 to 3 shown.
[0081] Figure 1 This is a diagram showing the photochromic process of the elastomers prepared in Examples 1 to 5 as the UV irradiation time increases.
[0082] Figure 2 The surface reflectivity of the elastomer prepared in Example 1 under different UV irradiation times.
[0083] Figure 3 The graph is a trend chart of the surface reflectivity variation at 471 nm of the elastomers prepared in Examples 1 to 5 under different UV irradiation times.
[0084] Fading process: The fading experiment of the elastomer prepared in Examples 1 to 5 and Comparative Example 3, the fading mechanism is that when exposed to air, the oxygen in the air reacts with the colored tungsten trioxide nanoparticles, oxidizing the pentavalent tungsten atoms in the nanoparticles during the coloring process to hexavalent tungsten atoms, thereby realizing the fading process. The fading process at room temperature is to place the sample after five minutes of coloring in an indoor environment, take pictures and measure the spectrum every other day for thirty consecutive days, and observe that the color of the sample has not changed significantly, and the surface reflectivity has not changed significantly; the fading process under the action of hydrogen peroxide solution is to apply 0.5% hydrogen peroxide solution on the surface of the sample after five minutes of coloring, observe and take pictures every 30 seconds, and it can be observed that the elastomer absorbs the hydrogen peroxide solution and swells violently, and the colored area fades significantly, and returns to the initial sky blue within twenty minutes.
[0085] Figure 4 The figure shows the fading process of the elastomers prepared in Examples 1 to 5 when treated with 5 wt % hydrogen peroxide solution.
[0086] Figure 5 This is a diagram showing the fading process of the elastomers prepared in Examples 1 to 5 when exposed to air.
[0087] Figure 6 This is a trend chart of the surface reflectivity change at 471 nm of the elastomers prepared in Examples 1 to 5 after exposure to air.
[0088] Figure 7 This is a graph showing the fading process of the elastomer prepared in Comparative Example 3 when exposed to air after being irradiated with UV light for 5 minutes.
[0089] Figure 8 This is a diagram showing the fading process of the elastomer prepared in Example 3 when treated with a 5 wt % hydrogen peroxide solution.
[0090] From the experimental results of Examples 1 to 5 and Comparative Example 3, it can be seen that the addition of urea has no significant effect on the coloring and fading properties of the photochromic material. The addition of urea has no significant effect on the coloring behavior of the photochromic material. During the fading process, the water absorption of urea can promote the absorption of the hydrogen peroxide solution by the elastomer, thereby accelerating the fading speed. Figure 4 As shown, Example 4 with the highest urea content almost completely faded after 7 minutes of hydrogen peroxide treatment; Example 5 with the lowest urea content, although the color became significantly lighter after 10 minutes of hydrogen peroxide treatment, a lighter color can still be observed. When the polymer monomer changes, it can be seen from Comparative Example 3 that the color of the obtained elastomer becomes significantly lighter to a level close to that before coloring after being exposed to air for 7 days, and it does not have the ability to color stably for a long time; at the same time, it also loses its response to hydrogen peroxide and does not have the ability to fade quickly.
[0091] When the photochromic unit changes, the Figures 9-10 It can be seen that both fade rapidly under the influence of air or visible light and do not have the ability to maintain stable coloration for a long time.
[0092] The mechanical properties of the photochromic elastomers prepared in Examples 1 to 5 were tested, and the method steps are as follows:
[0093] The mechanical properties test process was carried out in accordance with the national standard GB / T 528-2009. During the experiment, the sample was cut using a 1A dumbbell-shaped specimen cutter (total length 100 mm, narrow part length 20.0 mm, narrow part width 5.0 mm) specified in the national standard GB / T 528-2009. Before the measurement, the thickness of the sample was measured using a thickness gauge in accordance with the provisions of method A in the national standard GB / T 2941. After the cut sample was fixed on the tensile machine, the tensile machine automatically tested and output information such as breaking stress, breaking elongation and elastic modulus.
[0094] Mechanical properties test results are as follows Figures 11-12 shown.
[0095] Fig.11 The breaking stress and breaking elongation of the elastomers prepared in Examples 1 to 5.
[0096] Fig.12 is the elastic modulus of the elastomer prepared in Examples 1 to 5.
[0097] Test results based on mechanical properties Figures 11-12 It can be seen that urea has a significant effect on the mechanical properties of the elastomer. The increase of urea will reduce the modulus and fracture stress of the elastomer, that is, it becomes softer. However, the photochromic elastomer in Example 4 becomes hard and loses its elasticity because a large amount of urea is used, which precipitates in the elastomer and causes a significant increase in the modulus, thereby causing the photochromic elastomer to become hard and lose its elasticity.
[0098] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0099] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a photochromic elastomer having both long-term coloring and rapid fading properties, characterized in that the steps include: The initiator, the crosslinking agent and the urea are dissolved in water, and then the photochromic unit dispersion and the polymer monomer are added in sequence, and finally the initiator auxiliary agent is added, and after being mixed evenly, the mixture is allowed to stand for curing and dried to obtain the photochromic elastomer; The photochromic unit dispersion is prepared by dispersing the photochromic unit in water, with a mass fraction of 5 to 20%; the photochromic unit in the photochromic unit dispersion is tungsten trioxide; The polymer monomer is hydroxyethyl acrylate; The usage ratio of the polymer monomer and the photochromic unit dispersion is 4-20 mmol:0.5 mL; the molar ratio of the polymer monomer and urea is 4-20:0-20; The molar ratio of the polymer monomer, the initiator and the crosslinking agent is 4-20: 0.01-0.05: 0.002-0.1; the molar ratio of the initiator and the initiator auxiliary is 0.01-0.05: 0.01-0.
05.
2. The preparation method according to claim 1, characterized in that: The initiator is ammonium persulfate or potassium persulfate; the crosslinking agent is N,N-methylenebisacrylamide or polyethylene glycol diacrylate; and the initiator auxiliary is tetramethylethylenediamine.
3. The preparation method according to claim 1, characterized in that: The static curing time is 10 to 60 minutes.
4. The preparation method according to claim 1, characterized in that: The drying temperature is 40-80°C.
5. A photochromic elastomer prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the photochromic elastomer as claimed in claim 5 in long-term information storage and rapid erasure materials.
Citation Information
Patent Citations
Photochromic polymer compositions and articles thereof
AU2007201545A1
Crosslinked polyurethane containing photochromic diarylethene and application
CN107880238A